Kepastian Hukum Penerapan Restorative Justice terhadap Pengguna Narkotika yang Tidak Disertai Barang Bukti pada Tingkat Penyidikan di Kepolisian Daerah Banten - Darmansyah, Muhammad; Chandra, Tofik Yanuar; Basuki, Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Based on data from the Banten Province National Narcotics Agency, in 2023, 1,236 narcotics cases were recorded, with the number of users arrested reaching 1,486. Tangerang City and Tangerang Regency were recorded as the areas with the highest number of cases. This fact demonstrates the empirical reality that drug abuse is not only increasing in terms of numbers, but also in terms of complexity, including perpetrators being caught without evidence. The consequences of law enforcement have implications for overcrowding in detention centers and correctional institutions, with the number of inmates detained for narcotics cases in 2023 reaching 131,069. Meanwhile, ideal legal norms have been regulated through various provisions such as Law Number 35 of 2009 concerning Narcotics, specifically Articles 54 and 103, which provide space for drug abusers to undergo rehabilitation, rather than imprisonment. The research questions addressed in this study are the procedures for implementing restorative justice for drug users who are not accompanied by evidence at the investigation stage at the Banten Regional Police and the legal certainty of implementing restorative justice for drug users who are not accompanied by evidence at the investigation stage. In this study, the author uses the theory of legal certainty and the theory of restorative justice as analytical tools. The research method used is a normative juridical legal approach but supported by interviews with the Tangerang City Police Resort agency. This research uses a statute approach, a case approach, a conceptual approach, and an analytical approach which in principle are sourced from primary legal materials consisting of existing laws and case studies, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The legal material analysis technique uses grammatical interpretation techniques. The results of this study indicate that the procedures for implementing restorative justice for drug users differ between the Police and the National Narcotics Agency (BNN). This difference is not only administrative, but also indicates a paradigm difference in interpreting the law between the repressive-formalistic and rehabilitative-humanistic approaches. The legal certainty of implementing restorative justice for drug users without evidence at the investigation level creates procedural asynchronous implementation of restorative justice-based rehabilitation policies, particularly in the context of the Integrated Assessment Team (TAT). The lack of integration of administrative mechanisms and inter-agency coordination makes the implementation of TAT ineffective and uniform. The suggestion in this study is that the formal basis for handling cases between the Police and the BNN should be harmonized in terms of the preparation of integrated guidelines to avoid legal uncertainty and potentially violate the principle of equality before the law. The role of TAT needs to be optimized in terms of legal authority and inter-agency coordination, as administrative obstacles often cause assessments to be ineffective.